Melatonin alleviates chronic intermittent hypoxia-induced gastric mucosal injury via attenuation of oxidative stress and JNK-mediated apoptotic signaling in rats - Hong L. Ji; Hua L. Yu; Jia F. Luo; Xin R. Li; Cheng X. Nie; Tie J. Liu; Huan H. Jiang; Cong H. Liu; Jia B. Zhang; Xin H. Yuan; Xiao F. Song; Yue D. Li; et al. (PLoS ONE, 2026)
Background To investigate the mechanism of chronic intermittent hypoxia on gastric injury in rats and the intervening effect and possible mechanism of melatonin. Methods Forty-eight male Wistar rats were randomly divided into normal control, intermittent hypoxia, and melatonin treatment groups. Subgroups (n = 4 per time point) were treated for 2, 4, 6, and 8 weeks. Gastric tissue morphology, gastric juice pH, pepsin levels, oxidative stress markers (MDA and SOD), and the expression of JNK and apoptosis-related genes (Bax, Bcl-2) were assessed. Results The intermittent hypoxia group exhibited significant gastric mucosal damage, decreased pH, increased pepsin, elevated MDA, reduced SOD, and upregulation of JNK and Bax/Bcl-2 mRNA ratio. Melatonin treatment markedly alleviated these pathological and molecular changes compared to the intermittent hypoxia group ( P < 0.05). Conclusion Chronic intermittent hypoxia induces gastric mucosal injury, which is associated with oxidative stress imbalance and activation of JNK-mediated apoptotic signaling. Melatonin exerts a protective effect by enhancing antioxidant capacity and suppressing the JNK-Bax/Bcl-2 pathway.